2021
DOI: 10.1021/acs.macromol.1c01000
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Bottlebrush Supported Mono(phenoxy–imine) Metal Complexes: Synthesis and Ethylene Polymerization

Abstract: We report a poly­(norbornene-graft-styrene) (PNB-g-PS) supported mono­(phenoxy–imine) metal complex for ethylene polymerization. As a molecular bottlebrush (MB), PNB-g-PS was prepared via grafting-through ring-opening metathesis polymerization (ROMP) of the norbornenyl macromonomer. Postmodification reactions of PNB-g-PS were performed to incorporate phenoxy–imine type ligands in PS side chains, which were then coordinated with early transition metals to generate a series of MB supported mono­(phenoxy–imine) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…Compared with conventional linear polymers, MBs display many unique features, such as the nanoscale size, higher persistent length of the single chain, and reduced overlap of neighboring chains [ 104 ]. Chen and coworkers reported a poly(norbornene- graft -styrene) (PNB- g -PS)-supported mono(phenoxy-imine) metal complex for ethylene polymerization, as shown in Figure 13 a [ 79 ]. PNB- g -PS-Br was prepared via grafting-through ROMP of the norbornenyl macromonomer, which was readily prepared by ATRP.…”
Section: Applications Of Smps In Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with conventional linear polymers, MBs display many unique features, such as the nanoscale size, higher persistent length of the single chain, and reduced overlap of neighboring chains [ 104 ]. Chen and coworkers reported a poly(norbornene- graft -styrene) (PNB- g -PS)-supported mono(phenoxy-imine) metal complex for ethylene polymerization, as shown in Figure 13 a [ 79 ]. PNB- g -PS-Br was prepared via grafting-through ROMP of the norbornenyl macromonomer, which was readily prepared by ATRP.…”
Section: Applications Of Smps In Catalysismentioning
confidence: 99%
“…Ethylene polymerization using the molecular and the MB-supported catalysts. Reprinted from Ref [79]. with permission.…”
mentioning
confidence: 99%
“…Tremendous methods have been developed to prepare bimodal polymers. Compared with the physical blending method, the chemical synthetic method could prepare bimodal PEs with good miscibility due to synthesizing LMW and HMW chains in situ. In our previous work, well-defined linear unimodal and bimodal PEs with controllable molecular weights have been synthesized by a chain transfer polymerization method .…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed different applications that cover a wide range of fields like catalysis, storage media, electrolysis, sensing, and in electro‐optical devices 18–25 . Also, in the medical field, as anticancer, antimicrobial, and antiviral agents, metallopolymers were used 26–31 . The complex is formed by the combination of an atom or ion with complexing agents (anions) 32 .…”
Section: Introductionmentioning
confidence: 99%